Risky plastics and the limits to consumer responsibilization - Helene Cherrier (Cambridge Prisms: Plastics, 2023)
This paper highlights the limitations of the use of risk in plastic governance. First, plastic risk categorizations adapt, evolve, and shift, which creates ambiguities and insecurities for consumers about the responsible choices to be made. Second, the risk frame requires consumer agency to mitigate risk, a privilege many cannot afford. Third, the use of risk in plastic governance cedes power to dominant market actors who possess the capacity to blame others and use guilt appeal to alleviate their responsibility. The concluding remarks point to the importance of changing our minds about plastics. The argument is to stop thinking that plastics are flexible and malleable.